BIOMECHANICAL ASPECTS OF POSTURAL CONTROL OF THE HUMAN BODY - Strashko, Ye.Yu.; Morokhovets, H.Yu.; Stetsenko, S.А.; Berezhna, V.А.; Kondratieva, Ye.О.; Horsha, O.V.; Stetsuk, Ye.V. (World of Medicine and Biology, 2022)
The uterus is a muscle-elastic-collagen system of levers involved in stabilizing a woman's posture during pregnancy; being in an unusual state due to changes in the connective tissue elements of both the uterus and extrauterine structures. With the increase of the uterus during pregnancy, the recovery of the typical posture changes due to changes in its muscular and elastic apparatus and in elastic-collagen connections with the bones of the pelvis. It is important that the dense area of the ligaments is a collagen structure and is the least elastic component of this chain. The uterus is attached to the pelvis from the inside. In contrast, the areas of the external spiroid dynamic muscle chains are attached from the outside, thus entwining the body both homolaterally and heterolaterally. Based on the above, we hypothesize that these are synergistic and mutually competing biomechanical structures. Disturbance in the balance of these structures can lead to a suboptimal condition of the pregnant woman's body in statics and dynamics.
Keywords: postural control; diaphragm; uterus; center of gravity; muscle spirals; biomechanics